Deltamethrin rescues run down of K+ outward rectifying channels in Vicia faba guard cells - Horváth, Ferenc (Acta Biologica Szegediensis, 2002)
The dominant outward rectifier K+ currents were examined in protoplasts from Vicia faba guard cells. In whole-cell patch-clamp recordings, we generally observed that the conductance of the K+ inward and the outward rectifier gradually decreases. As a consequence of this run down a new steady state was achieved which was 90±5% lower than that obtained at the beginning of the recording. The run down of the outward rectifier could be greatly reduced by pretreating protoplasts either with the membrane permeable drug deltamethrin or by perfusing protoplasts with a pipette solution containing 5pM cydosporine A. Furthermore, after the rundown the conductance of the outward rectifier could be partially restored upon addition of 5pM deltamethrin to the bath medium. Since deltamethrin and cydosporine A are established inhibitors of the calcium sensitive phosphatas e calcineurin, the data argue for a participation of this type of phosphatase in the control of the activity of K+ outward rectifier channel in guard cells.